The Impact of Market Capitalization and Dividend Policy on Firm Value (A Study of Food and Beverage Companies Listed on the Indonesia Stock Exchange from 2019 to 2024 - Aswandi Jufry; Ni Made Suwitri Parwati; Moh. Iqbal Bakry; Muhammad Ilham Pakawaru (Danadyaksa: Post Modern Economy Journal, 2026)
Firm value is an important indicator for investors in assessing corporate performance and future prospects. However, previous studies on the relationship between market capitalization, dividend policy, and firm value have produced inconsistent results. This study aims to examine the effect of market capitalization and dividend policy on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2024 period. This study employed a quantitative explanatory approach using secondary data obtained from annual reports and the Indonesia Stock Exchange. A purposive sampling technique was applied, resulting in 18 companies as the research sample. Data were analyzed using multiple linear regression with SPSS Version 25. The results indicate that market capitalization has a positive and significant effect on firm value, while dividend policy has a positive but insignificant effect. These findings suggest that investors place greater emphasis on market valuation than on dividend distribution when assessing firm value. This study contributes to the corporate finance literature by providing updated empirical evidence on the determinants of firm value in Indonesia's food and beverage sector and offers practical insights for managers and investors.